THE DIDACTIC SYSTEM FOR DEVELOPING FUTURE TEACHERS’ CREATIVITY BASED ON CREATIVE TASKS (Eureka Journal of Education & Learning Technologies, 2026)
This article presents observations on the socio-philosophical and pedagogical interpretation of the concepts of "creativity" and "creative task". The article also analyzes the presentation of the concepts of creativity and creative task in various sources from the author's point of view and presents the author's definitions of these concepts from a personal point of view.
Keywords: Creativity, creative tasks, development, creative skills, modern education, educational process, teacher.